A Case Concerning Children's False Memories of Abuse: Recommendations Regarding Expert Witness Work. Issue 3 (4th May 2017) - Otgaar, Henry; de Ruiter, Corine; Howe, Mark L.; Hoetmer, Lisanne; van Reekum, Patricia
Abstract : Expert witnesses can play a major role in legal cases concerning the reliability of statements. Abuse cases frequently contain only the memories of eyewitnesses/victims without the presence of physical evidence. Here, it is of the utmost importance that expert witnesses use scientific evidence for their expert opinion. In this case report, a case is described in which 20 children reported being sexually abused by the same teachers at their elementary school. The investigative steps that were taken by the police and school authorities are reviewed, including how they probably affected memory. In order to provide a sound expert opinion regarding the reliability of these statements, three recommendations are proposed. To reduce the effect of confirmation bias and increase objectivity, it is argued that expert witnesses' reports should contain alternative scenarios, be checked by another expert, and focus on the origin and context of the first statement.